2020
DOI: 10.1016/j.bbih.2020.100054
|View full text |Cite
|
Sign up to set email alerts
|

Prevention and treatment of HIV infection and cognitive disease in mice by innate immune responses

Abstract: HIV associated neurocognitive impairment afflicts roughly half of infected individuals on antiretroviral therapy. This disease currently has no treatment. We have previously shown that type I interferon is induced by and partially controls infection and neuropathogenesis in mice infected by chimeric HIV, EcoHIV. Here we investigate the intentional ligation of the pattern recognition receptor Toll-like receptor 3 (TLR3) by polyinosinic-polycytidylic acid (poly I:C) for its ability to prevent or control infectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 69 publications
6
15
0
Order By: Relevance
“…Indeed, we previously showed that leukocytes that infiltrate the brains of infected mice carry integrated EcoHIV DNA 15 . The likely signal for this migration is CCL2; it is the major monocyte chemokine 22 and is highly induced by EcoHIV infection in mouse macrophages 16 and in macrophages/microglia in the EcoHIV-or HIV-infected brain 10 , 41 . Direct injection of CCL2 into mouse hippocampus is a highly potent inducer of monocyte migration to the site 42 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, we previously showed that leukocytes that infiltrate the brains of infected mice carry integrated EcoHIV DNA 15 . The likely signal for this migration is CCL2; it is the major monocyte chemokine 22 and is highly induced by EcoHIV infection in mouse macrophages 16 and in macrophages/microglia in the EcoHIV-or HIV-infected brain 10 , 41 . Direct injection of CCL2 into mouse hippocampus is a highly potent inducer of monocyte migration to the site 42 .…”
Section: Resultsmentioning
confidence: 99%
“…Intracranial injection of EcoHIV into mice revealed that the virus mainly infects macrophage/microglial cells and not neurons in the brain 7 , 9 , a result reproduced using RNAscope in EcoHIV infected rats 11 . The control of EcoHIV replication in mice was attributed to both innate 7 , 16 and HIV specific CD8 + T cell immune responses 17 . Other research suggests that EcoHIV, like HIV, can infect neuronal progenitor cells 18 and pericytes 19 in the central nervous system.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, we previously showed that leukocytes that in ltrate the brains of infected mice carry integrated EcoHIV DNA 28 . The likely signal for this migration is CCL2; it is the major monocyte chemokine 42 and is highly induced by EcoHIV infection in mouse macrophages 43 and in astrocytes and monocytes/microglia in the HIV or EcoHIV-infected brain 8, 44 . We exploited a mouse strain with knockout of CCL2 and compared the course of its EcoHIV infection to that of wildtype C57BL/6 mice (Fig.…”
Section: Monocyte Chemotaxis To Ccl2 Contributes To Ecohiv Ncimentioning
confidence: 99%
“…HIV-NCI is a spectrum of cognitive deficits that negatively impact the quality of life for PWH and is an independent risk factor for morbidity and mortality (5,6,9,10). Despite several successful treatment attempts for HIV-NCI in preclinical animal models no approved therapy for NCI in PWH has emerged (11)(12)(13)(14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%